FP-LAPW calculations of ground state properties for AlN, GaN and InN compounds - Daoudi, B.; Sehil, M.; Boukraa, A.; Abid, H. (Universiti Malaysia Perlis, 2008)
Link to publisher's homepage at http://www.unimap.edu.my/ ; Open access only applicable for vol. 1; issue 1, 2008.